Postpartum Uterine Wound Dehiscence Leading to Secondary PPH: Unusual Sequelae - Rinku Sengupta Dhar; Renu Misra (Hindawi Limited, 2012)
Secondary postpartum haemorrhage due to partial or complete dehiscence of uterine wound after caesarean section is unusual. Authors present here a patient with secondary postpartum haemorrhage following uterine dehiscence after caesarean delivery. Conservative management failed to control the bleeding, and she eventually needed hysterectomy. All women who have significant PPH following caesarean should undergo evaluation for any defect in the scar. Scar dehiscence has been diagnosed and repaired after many years of caesarean section in women with persistent abnormal bleeding. Therefore, this condition may have long-term implication if missed postpartum.